Onto the Fourth Year - Thapa, Shyam; Amgain, Kapil (Europasian Journal of Medical Sciences, 2022)
The Europasian Journal of Medical Sciences (EJMS) is entering into its fourth year, and we begin this fourth year with several changes in the management, policies and review process. First, the editorial board has been reconstituted to serve for the next two years, from 2022 to 2024. The editorial office represents a mix of previous and new associates. On behalf of the EJMS, we welcome each and every member to the new editorial board. We remain grateful to the many members who spent their time reviewing papers submitted for consideration. We recognize that it is the dedication of their time that makes the difference in ensuring that the papers submitted meet the journal’s rigorous standards. We welcome the expanded network of advisors offering their time and support. At the same time, we gratefully thank all the members who have served in different capacities in previous years. As subscribers and readers will note, the EJMS now includes academic editors representing various backgrounds. The engagement of these academic editors will, we believe, contribute to improving and strengthening the quality of the materials published in the journal. The associate editors will have the support of assistant editors in the review process.